Intensity-Modulated Radiation Therapy for Esthesioneuroblastoma: 10-Year Experience of a Single Institute - Bao, Cihang; Hu, Weixu; Hu, Jiyi; Dong, Yuanli; Lu, Jiade J.; Kong, Lin (Frontiers in Oncology, 2020)
Objectives: To evaluate efficacy and safety of intensity-modulated radiotherapy (IMRT) in the management of esthesioneuroblastoma (ENB). Methods and Materials: A retrospectively analysis of 52 ENB patients treated with IMRT between 8/2008 and 8/2018 was performed. Thirteen of the 44 patients (29.5%) with newly diagnosed and 2 of the 8 patients with recurrent disease presented regional lymph node metastasis. The median dose of IMRT was 66 (range 52.5-75) Gy for all patients. Elective nodal irradiation (ENI) was provided to all excluding 6 patients in this cohort. Results: With a median follow-up time of 32.5 (6~121) months, the 3-year overall survival (OS), progression-free survival (PFS), local progression-free survival (LPFS), regional progression-free survival (RPFS) and distant metastasis-free survival (DMFS) rates for the entire cohort were 89.7%, 69.5%, 89.7%, 95.1%, and 85.4 %, respectively. Multivariate analysis revealed that N-classification (N- vs. N+) at presentation was the only significant prognosticators for PFS. No significant prognosticator was identified for other survival outcome. No severe (i.e., grade 3 or 4) IMRT-induced acute toxicity was observed. Severe late toxicities were infrequent (11.5%), which included dysosmia (3.8%), hearing loss (3.8%), radiation brain injury (1.9%), and temporal lobe necrosis (1.9%). Moreover, late ocular toxicity secondary to IMRT was not observed. Conclusion: IMRT produced acceptable 3-year outcomes in terms of OS (89.7%), LPFS (89.7%), and RPFS (95.1%) rates without substantial late adverse effects. Further investigations for a more effective systemic strategy for distant disease control as well as a precision radiation technique for further improvement in local control are needed.